2007
DOI: 10.1021/ja0692940
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen-Bonding and π−π Base-Stacking Interactions Are Coupled in DNA, As Suggested by Calculated and Experimental Trans-Hbond Deuterium Isotope Shifts

Abstract: Computational and experimental trans-Hbond deuterium isotope shifts suggest that Hbonding and electronic base-stacking interactions, although largely orthogonal, are coupled in B-form DNA duplexes. For an A:T base pair, the Hbond is shorter and stronger in the RAR:YTY than YAY:RTR context. This difference is due to the greater anharmonicity of the N3−H3 vibrational potential of the thymine in RAR:YTY, which arises from electronic interactions between A:T and adjacent bases. As predicted by the calculations, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
38
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 19 publications
2
38
0
Order By: Relevance
“…This research has revealed that deviations in these structural parameters are sequence dependent 710. Also, thermodynamic studies have suggested tentatively that hydrogen bonds and base‐stacking interactions are coupled in DNA11 and the measurements of the two‐bond deuterium isotope shift, 2 Δ 13 C,12 suggest that the hydrogen‐bond strengths in the DNA base pairs are modulated by the electronic interactions with adjacent bases to different extents depending on sequence context.…”
Section: Introductionmentioning
confidence: 92%
“…This research has revealed that deviations in these structural parameters are sequence dependent 710. Also, thermodynamic studies have suggested tentatively that hydrogen bonds and base‐stacking interactions are coupled in DNA11 and the measurements of the two‐bond deuterium isotope shift, 2 Δ 13 C,12 suggest that the hydrogen‐bond strengths in the DNA base pairs are modulated by the electronic interactions with adjacent bases to different extents depending on sequence context.…”
Section: Introductionmentioning
confidence: 92%
“…The results indicate that upon substitution of T with Br U, a PNA·dsRNA triplex containing C + ·G-C base triples may become more resistant against high-pH destabilization. It is likely that enhancing hydrogen bonding and stacking involving X U·A-U base triples (compared to PNAs without X U substitution) may in turn favor C + ·G-C base triple formation and reduce the pH dependence by further shifting up the pK a of C residues in a PNA·dsRNA triplex through the coupling between stacking and hydrogen bonding interactions (78). However, the K d value of PNA FU-3,5 binding to rHP1 is still relatively pH dependent 0.3 and 4.7 M at pH 7.5 and 8.0, respectively), probably because F U stabilizes triplex formation mainly through enhancing base triple formation but not by shifting the pK a of adjacent C residues.…”
Section: Substitution Of T With U or Halouracils In An Unmodified Pnamentioning
confidence: 99%
“…Compared to P1, the singly-and doubly-modified PNA sequences have higher melting temperatures (based on the heating curves), with Cl U and Br U modifications being the most stabilizing ( Figure 4C, D). Compared to F U base, Cl U and Br U may be more ideal for optimizing the coupled stacking and hydrogen bonding interactions (78,79) for the sequences tested here, with the PNAs containing pyrimidine residues only. The stabilization effect of X U substitution on PNA-RNA duplex was also observed previously for a different PNA sequence (with the X U residue flanked by two G residues), although relatively less variation among F U, Br U, and Cl U was observed 5 (F, H).…”
Section: Substitution Of T With U or Halouracils In An Unmodified Pnamentioning
confidence: 99%
“…NMR spectroscopy is a particularly powerful tool for the study of H-bonding in biomolecules, which can be probed by chemical shifts, 21 NMR analysis of pressure-induced unfolding, 22 H-bond J-couplings, 2327 H/D fractionation factors 2832 and isotope shifts. 28, 3334 …”
mentioning
confidence: 99%